Atrial fibrillation screening: feasible approaches and implementation challenges across Europe. Issue 4 (29th December 2021) - Engler, D; Hanson, C; Desteghe, L; Boriani, G; Diederichsen, S Z; Freedman, B; Pala, E; Potpara, T; Witt, H; Heidbuchel, H; Neubeck, L; Schnabel, R B; et al.
Abstract: Background: Atrial fibrillation (AF) screening has the potential to increase early detection and possibly reduce complications of AF. Guidelines recommend screening, but the most appropriate approaches are unknown. Purpose: We aimed to explore the views of stakeholders across Europe about the opportunities and challenges of implementing four different AF screening scenarios. Method: This qualitative study included 21 semi-structured interviews with healthcare professionals and regulators potentially involved in AF screening implementation in nine European countries. Data were analysed using thematic analysis. Results: Three themes evolved. 1) Current approaches to screening: there are no national AF screening programmes, with most AF detected in symptomatic patients. Patient-led screening exists via personal devices, creating screening inequity by the reach of screening programmes being limited to those who access healthcare services. 2) Feasibility of screening approaches: single time point opportunistic screening in primary care using single lead ECG devices was considered the most feasible approach and AF screening may be possible in previously unexplored settings such as dentists and podiatrists. Software algorithms may aid identification of patients suitable for screening and telehealth services have the potential to support diagnosis. However, there is a need for advocacy to encourage the use of telehealth to aid AF diagnosis, and training for screening familiarisation and troubleshooting. 3) Implementation requirements: sufficient evidence of benefit is required. National rather than pan-European screening processes must be developed due to different payment mechanisms and health service regulations. There is concern that the rapid spread of wearable devices for heart rate monitoring may increase workload due to false positives in low risk populations for AF. Data security and inclusivity for those without access to primary care or personal devices must be addressed. Conclusions: There is an overall awareness of AF screening. Opportunistic screening appears to be most feasible across Europe. Challenges that need to be addressed concern health inequalities, identification of best target groups for screening, streamlined processes, the need for evidence of benefit, and a tailored approach adapted to national realities. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): H2020